2016
DOI: 10.4269/ajtmh.16-0343
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis in Khyber Pakhtunkhwa Province of Pakistan: Clinical Diversity and Species-Level Diagnosis

Abstract: This study primarily aimed to identify the causative species of cutaneous leishmaniasis (CL) in the Khyber Pakhtunkhwa Province of Pakistan and to distinguish any species-specific variation in clinical manifestation of CL. Diagnostic performance of different techniques for identifying CL was assessed. Isolates of Leishmania spp. were detected by in vitro culture, polymerase chain reaction (PCR) on DNA extracted from dried filter papers and microscopic examination of direct lesion smears from patients visiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 43 publications
5
45
2
Order By: Relevance
“…This is in agreement with previous reports published in Sri Lanka [12]. The clinical appearance of cutaneous lesions varies depending of the immunity of the patient [33] and the species or strain of the causative agent [34]. The study reported a considerably large proportion of leishmaniasis patients among clinically suspected patients.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with previous reports published in Sri Lanka [12]. The clinical appearance of cutaneous lesions varies depending of the immunity of the patient [33] and the species or strain of the causative agent [34]. The study reported a considerably large proportion of leishmaniasis patients among clinically suspected patients.…”
Section: Discussionsupporting
confidence: 91%
“…P. papatasi is also susceptible to carry L. tropica and is widely distributed in different parts of Pakistan, including Khyber Pakhtunkhwa Province ( 8 ). A previous team had reported L. infantum in 2 army personnel deployed in Waziristan, ( 9 ) but the present detailed study ruled out its presence.…”
contrasting
confidence: 64%
“…Pakistan is particularly important with respect to leishmaniasis due to occurrence of both ACL and ZCL caused by L. tropica and L. major . The majority of leishmaniasis cases are ACL caused by L. tropica ; confirmed by the currebt study thus deeming L. tropica responsible for the occurrence of disease in the study area . Human population density plays a key role in the spread and distribution of CL, for two major reasons: It is a variable of basic reproduction number for vector‐borne disease, and humans are a host reservoir for the ACL parasite, so ACL can be predicted to be more prevalent in areas with high‐population density (Figure c).…”
Section: Discussionmentioning
confidence: 74%